War and Peace in Mindanao Tracing the Roots of Historical Injustice - Maboloc, Christopher Ryan (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Structural injustice appears normalized and legitimized in modern societal culture. The Mindanao problem is not a religious conflict between Christians and Muslims. War and peace in Mindanao is a question of historical and structural injustice. Portraying the Christian and Muslim divide as some form of religious war silences the suffering of its Indigenous Peoples. The exclusion of the Lumad is due to a type of violence against their identity. Philippine society labels indigenous peoples as illiterate and the Muslim Filipino as violent. In the Filipino socio-cultural hierarchy, the Christian is at the top whereas in the middle lies the Muslim Filipino. Powerless and without any voice, at the bottom dwells the Lumad. There was no peace in the past because of this moral divide. Peace is not just the absence of conflict. It is a process that involves the full recognition of human dignity and the respect for basic human rights. It can only be achieved if it is inclusive, which means that it is meant for all human beings and not just to satisfy the economic or political demands of a dominant group. This is why inclusion cannot be limited to the distribution of resources. While politics caters to the satisfaction of power players, peace is can only be rooted in the solidarity of a people as one nation.